THE PROBLEM OF ETHNIC HISTORY: THEORETICAL - METHODOLOGICAL APPROACHES (On the example of ethnic history of Kungirats) - Murtoz Usmanov (Journal Park Publishing, 2023)
In the science of ethnology, there are many terms and theoretical issues related to the way of life of peoples, without researching them, it is difficult to express an opinion about ethnic history. For example, in relation to calls, researchers more often use the terms ethnographic group or subethnos. Well-known ethnographer K. According to Shaniozov, an ethnographic group is one of a certain ethnos (an integral part of a people or a nation, one of its constituent divisions), which differed in some of its features, language dialect, economic activity, and some aspects of lifestyle[1]. Ethnographic group is usually formed as a result of one tribe, nation or nation mixing with another people, going to another place, becoming part of the local people and living together with it. For example, the bells within the Uzbeks are an ethnographic group. Sometimes an ethnographic group was formed as a result of separating from its people and joining another ethnic group. A large number of ethnic groups of this type have come over the centuries, lived among the local people, accepted their traditions and culture, and mixed with it. However, a certain part of them has preserved some features of their language, identity and material culture.
Keywords: Ethnographic group, ethnic group, ethnos, kungrat, subethnos ethnology, tribe, nation, aksakal, nationality, village, country, land, homeland, Boysun-kungrat country, Jiydali-Boysun, kappa, tent, lochig (change houses for temporary housing).